Utilization of IoT for Soil Moisture and Temperature Monitoring System for Onion Growth - Izak Habel Wayangkau; Yosehi Mekiuw; Rachmat Rachmat; Suwarjono Suwarjono; Hariyanto Hariyanto (Emerging Science Journal, 2020)
The use of IoT in precision agriculture is very important in the process of increasing crop production. The local supply of onions in Merauke Regency have not fulfilled the demand, thus the high price in the market. Most of the demand for onion are still fulfilled from outside the region, as the production of local farmers has not been optimal. The weather has been identified as one of the factors that affect the quality of onion production. This study aims to create an automatic monitoring system based on an Arduino microcontroller to measure soil moisture and temperature in onion patches. The method used is to design an automatic monitoring device to determine soil moisture and temperature so that it can provide information about the growth and maintenance of onion patches. The Arduino microcontroller is connected to a reading sensor that is integrated with component devices to maintain a stable temperature and soil moisture. All devices and components are designed to operate in a custom-made environment in the form of a greenhouse prototype. The results of this study indicate that the tool and system are capable of capturing the soil moisture and temperature, as well as maintaining the soil moisture and temperature within certain parameters, in cloudy, wet and hot weather conditions. Doi: 10.28991/esj-2021-SP1-07 Full Text: PDF